Peaceful Way Before Separation: Examining the Effectiveness and Procedures of Mediation in Resolving Divorce Disputes in Religious Courts - Safrudin, Safrudin (Strata Social and Humanities Studies, 2024)
The high divorce rate demands effective and peaceful dispute resolution efforts, primarily through mediation in court. This study aims to examine the effectiveness and procedures of mediation in court in resolving divorce disputes in a structured and peaceful manner. Using a normative legal research method with a descriptive-analytical approach, this study analyzes laws and regulations related to mediation procedures in Indonesia, including Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2016 concerning Mediation Procedures in Court. The study's results indicate that mediation has proven effective in reconciling couples about to divorce. According to the Regulation of the Minister of Religious Affairs Number 1 of 2016, the mediation procedure in the Religious Court begins with pre-mediation, continues with the mediation process facilitated by the mediator, and ends with the recording of the mediation conclusion. The success of mediation is marked by a peace agreement stated in a peace deed. This study suggests the importance of increasing the capacity of mediators, socializing the benefits of mediation, and developing innovative mediation models to optimize the function of mediation as a means of resolving divorce disputes effectively, efficiently, and peacefully.